1990
DOI: 10.1084/jem.172.3.997
|View full text |Cite
|
Sign up to set email alerts
|

Mouse plasmacytoma growth in vivo: enhancement by interleukin 6 (IL-6) and inhibition by antibodies directed against IL-6 or its receptor.

Abstract: SummaryMurine plasmacytomas show a striking dependence on interleukin 6 (IL6) for their growth in vitro. Here, we present evidence suggesting that IL6 also plays an essential role in the in vivo development of these tumors . This conclusion is based on the finding that the tumorigenicity of an IL-6-dependent plasmacytoma cell line was increased -100-fold on transfection with an IL-6 expression vector, whereas it was inhibited in animals treated with monoclonal antibodies capable of blocking the binding of IL6 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
53
0

Year Published

1991
1991
2010
2010

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 114 publications
(54 citation statements)
references
References 11 publications
1
53
0
Order By: Relevance
“…For instance, transfection of the human IL-6 gene in murine plasmacytoma or hybridoma led to increased tumorigenicity (21,22). On the other hand, IL-6 gene transgenic mice exhibit a striking plasmacytosis but no transplantable plasma cell tumor could be obtained (23).…”
Section: Resultsmentioning
confidence: 99%
“…For instance, transfection of the human IL-6 gene in murine plasmacytoma or hybridoma led to increased tumorigenicity (21,22). On the other hand, IL-6 gene transgenic mice exhibit a striking plasmacytosis but no transplantable plasma cell tumor could be obtained (23).…”
Section: Resultsmentioning
confidence: 99%
“…27 Critical evidence for the involvement of IL-6 in inflammation-induced peritoneal plasmacytomagenesis was first obtained in studies with C mice, showing that tumor growth is enhanced by exogenous IL-6 but inhibited by antibodies to IL-6 or its receptor. 28 Subsequent work demonstrated that C mice homozygous for a null allele of Il6 are resistant to both pristane-induced peritoneal PCT 29 and peritoneal PCT accelerated by a Myc/Raf retrovirus. 30 Conversely, C mice carrying the H2-L d -IL6 TG develop PCT spontaneously without a requirement for peritoneal inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…The IL-6 receptor system consists of two functional molecules, an 80-kDa ligand-binding chain (IL-6R) and a 130-kDa nonligand-binding but signal-transducing chain (gp130). The anti-IL-6R Ab blocks the binding of IL-6 to the IL-6R (38,39). The anti-IL-6R Ab or the control Ab was i.p.…”
Section: Elimination Of Il-6 Signaling Reduces Liver Toxicitymentioning
confidence: 99%